The Competence in the Digital Era in Improving Public Service Performance - Nur, Hafni Rizanuddin (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This study will explain the competence of human resources in the digital era to influence better performance. The human resources needed by the industry today are those who have competence in using digital technology. This competency is to realize intelligent factories, such as the Internet of Things (IoT). The era of the industrial revolution 4.0 opens opportunities for human resources (HR) to have skills following the latest technological developments. For this reason, civil servants who are state apparatus must be able to answer the challenges and master competencies in the digitalization era, including complex problem solving, critical thinking, creativity, human resource management, coordination with others, emotional intelligence, judgment and decision making, orientation service, Negotiation, and cognitive flexibility. This study uses quantitative research methods through the distribution of questionnaires or questionnaires to respondents who have been determined using sampling. The analytical technique used is structural equation modeling analysis. The results show that the appropriate competencies in the digitalization have a significant influence on the performance of public services.